2020
DOI: 10.1186/s12931-020-01339-7
|View full text |Cite
|
Sign up to set email alerts
|

A positron emission tomography imaging study to confirm target engagement in the lungs of patients with idiopathic pulmonary fibrosis following a single dose of a novel inhaled αvβ6 integrin inhibitor

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease with poor prognosis and a significant unmet medical need. This study evaluated the safety, pharmacokinetics (PK) and target engagement in the lungs, of GSK3008348, a novel inhaled alpha-v beta-6 (αvβ6) integrin inhibitor, in participants with IPF. Methods: This was a phase 1b, randomised, double-blind (sponsor unblind) study, conducted in the UK (two clinical sites, one imaging unit) between June 2017 and July 2018 (NCT03069… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…The aim of this study was to fully characterize GSK3008348 and generate translational drug discovery biomarkers that will facilitate the performance of future clinical trials. To date, GSK3008348 has been shown to be safe and well tolerated in phase I healthy volunteer studies 24 and has completed a phase Ib study, demonstrating target engagement of the αvβ6 integrin in IPF patients 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to fully characterize GSK3008348 and generate translational drug discovery biomarkers that will facilitate the performance of future clinical trials. To date, GSK3008348 has been shown to be safe and well tolerated in phase I healthy volunteer studies 24 and has completed a phase Ib study, demonstrating target engagement of the αvβ6 integrin in IPF patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…NanoSPECT-CT imaging studies using A20FMDV2 in saline and bleomycin-treated mice demonstrated the dose-and time-dependent engagement of GSK3008348 with αvβ6 in an in vivo model of lung fibrosis. The quantification of αvβ6 integrin upregulation in IPF and the profiling of GSK3008348 binding to the integrin in diseased tissue will allow this pre-clinical work to be translated to clinical studies in IPF 25,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a bleomycin-induced murine lung fibrosis model, GSK300834 was used as an inhalable therapeutic and reduced lung collagen deposition and fibrosis progression [ 475 ]. The results of a small phase Ib study (eight patients) indicate that nebulized dosing with GSK300834 was safe and led to successful target engagement [ 478 ]. Future clinical studies with GSK300834 are eagerly awaited.…”
Section: Integrin Targeting In Non-cancer Diseasesmentioning
confidence: 99%
“…18 F-Fluorodeoxyglucose ( 18 F-FDG) is the most widely available and commonly used PET tracer and is predominantly employed to assess lung inflammation and fibrosis-related processes for both research and clinical purposes. New molecularly-targeted PET tracers are also being developed to support the respiratory drug development process, with a recent publication demonstrating the additional potential for PET imaging to assess drug target engagement in the lungs (5).…”
Section: Introductionmentioning
confidence: 99%